Developing Intercultural Competence through the Study of National and World Literature - Paladian, Kristiniia; Paladian, Yuliana (Didactica Danubiensis, 2026)
The growing trend toward globalization creates a unique challenge for educators in preparing their students to function within and respond appropriately to the increasing diversity of the world around them. This paper aims to establish a theoretical-methodological framework for intercultural educational policies and to focus on the potential of literature classes as an integral part of developing intercultural competency. The study builds upon the principles of the intercultural paradigm centered on alterity of M. Abdallah-Pretceille and the integrates established models proposed by P. Batelaan and A. Fantini. A unique context for examining identity and alterity is created through a combination of national literature and the study of world literature. While students learn about their own culture through the study of literature from their own country, they will also be introduced to different cultures through the study of literature from other countries. As students interact with various types of literature, they will develop a greater understanding of the cultural perspectives of others and move beyond simply appreciating the artistry of a literary text to recognising how literature can assist them in breaking down stereotypes and building empathy toward people from other cultures.